2015
DOI: 10.1016/j.sbspro.2015.01.650
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness as an Intervention for Improving Academic Success among Students with Executive Functioning Disorders

Abstract: College attendance has increasingly become a seemingly mandatory next step following high school: employment, promotion, and career-related skills frequently demand post-secondary training. As the college attendance rate has increased, the rate of college attendees with diagnosed learning disabilities or learning challenges has followed suit (Connor, 2012). Time management, including the abilities to focus attention and reach incremental goals, are critical to college success (Al-Harthy, Qaboos, & Was, 2013). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
1
31
1
Order By: Relevance
“…Compared to findings in the literature review, this research supported the overall effectiveness of a mindfulness-based intervention for students with special needs (Beauchemin, Hutchins, & Patterson, 2008;Carboni, Roach, & Frederick, 2013;Elias, 2004;McCloskey, 2015), in terms of improving students' attention, behavior, and self-perception. Of the ten participating students, seven students displayed some level of improvement in their attention and behavior in their general education classes, based on observations and teacher feedback.…”
Section: Chapter 5 Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Compared to findings in the literature review, this research supported the overall effectiveness of a mindfulness-based intervention for students with special needs (Beauchemin, Hutchins, & Patterson, 2008;Carboni, Roach, & Frederick, 2013;Elias, 2004;McCloskey, 2015), in terms of improving students' attention, behavior, and self-perception. Of the ten participating students, seven students displayed some level of improvement in their attention and behavior in their general education classes, based on observations and teacher feedback.…”
Section: Chapter 5 Discussionsupporting
confidence: 60%
“…While there are studies that have examined the effects of mindfulness with students, there is little to no research studies that have examined the effectiveness of an MBI on middle school students with special needs. Previous studies regarding mindfulness with special education students focus on students at the elementary, high school, and college levels (Beauchemin, Hutchins, & Patterson, 2008;Carboni, Roach, & Frederick, 2013;Malow & Austin, 2016;Elias, 2004;McCloskey, 2015;Malboeuf-Hurtubise, Lacourse, Taylor, Joussemet, & Amor, 2016).…”
Section: Statement Of Purposementioning
confidence: 99%
See 1 more Smart Citation
“…For example, van der Riet et al ., Frank et al ., Poulin, Zenner et al ., Bamber and Schneider, and McCloskey showed the effectiveness of mindfulness interventions on test anxiety of students. [ 23 24 25 26 27 28 ] Vøllestad et al . also found that MBSR can be useful in keeping anxiety symptoms in a balanced level in people with anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In response, many universities are developing strategies designed to improve student mental health (Greenberg et al, 2003). They are paying particular attention to mindfulness because there is increasing evidence that 'mindful learning' addresses student mental health and general coping abilities (Collard, Avny, & Boniwelly, 2008;Hassed, de Lisle, Sullivan, & Pier, 2009;Kang, Choi, & Ryu, 2009;Lynch, Gander, Kohls, Kudielka, & Walach, 2011), and also enhances students' cognitive and socio-emotional capabilities and improves their general well-being and academic performance (Hassed & Chambers, 2014;McCloskey, 2015;Mrazek, Franklin, Phillips, Baird, & Schooler, 2013;Ritchhart & Perkins, 2000;Zeidan, Johnson, Diamond, David, & Goolkasian, 2010). A number of Australian universities (such as Monash University, the Australian National University and the University of South Australia) are thus offering mindfulness programs to help students both with stress management and to develop cognitive strategies to enhance academic performance (Hassed & Chambers, 2014).…”
Section: Introductionmentioning
confidence: 99%